A novel functional interplay between Progesterone Receptor‐B and PTEN, via AKT, modulates autophagy in breast cancer cells. Issue 11 (12th September 2014) - De Amicis, Francesca; Guido, Carmela; Santoro, Marta; Lanzino, Marilena; Panza, Salvatore; Avena, Paola; Panno, Maria Luisa; Perrotta, Ida; Aquila, Saveria; Andò, Sebastiano
Abstract The tumour suppressor activity of the phosphatase and tensin homologue on chromosome 10 (PTEN) is subject of intense investigative efforts, although limited information on its regulation in breast cancer is available. Herein, we report that, in breast cancer cells, progesterone (OHPg), through its cognate receptor PR‐B, positively modulates PTEN expression by inducing its mRNA and protein levels, and increasing PTEN‐promoter activity. The OHPg‐dependent up‐regulation of PTEN gene activity requires binding of the PR‐B to an Sp1‐rich region within the PTEN gene promoter. Indeed, ChIP and EMSA analyses showed that OHPg treatment induced the occupancy of PTEN promoter by PR and Sp1 together with transcriptional coactivators such as SRC1 and CBP. PR‐B isoform knockdown abolished the complex formation indicating its specific involvement. The OHPg/PR‐B dependent induction of PTEN causes the down‐regulation of PI3K/AKT signal, switching on the autophagy process through an enhanced expression of UVRAG and leading to a reduced cell survival. Altogether these findings highlight a novel functional connection between OHPg/PR‐B and tumour suppressor pathways in breast cancer.